2015
DOI: 10.7314/apjcp.2015.16.2.641
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic Stress Disorder and Post-traumatic Growth in Breast Cancer Patients - a Systematic Review

Abstract: Breast cancer (BC) is potentially a traumatic stressor which may be associated with negative outcomes, such as post-traumatic stress disorder (PTSD) or positive changes, such as post-traumatic growth (PTG). This study aims to identify the core issues of BC related PTSD, PTG and psychological distress by interrogating the literature in BC survivors. We have also highlighted issues related to the assessment, diagnosis and clinical management of PTSD and PTG. The authors systematically reviewed studies published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 40 publications
2
40
0
3
Order By: Relevance
“…43 The experience of a diagnosis of cancer and its related treatments reportedly can lead to symptoms of posttraumatic stress in 7.3% to 35.2% of patients with cancer. 44 In the current study, cancer-specific stress (ie, total score on the IES-R) uniquely explained approximately 3.2% of the variance in symptom burden. Similarly, among survivors of leukemia, higher levels of cancer-specific stress were associated with higher levels of depressive symptoms, sleep problems, and fatigue interference.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…43 The experience of a diagnosis of cancer and its related treatments reportedly can lead to symptoms of posttraumatic stress in 7.3% to 35.2% of patients with cancer. 44 In the current study, cancer-specific stress (ie, total score on the IES-R) uniquely explained approximately 3.2% of the variance in symptom burden. Similarly, among survivors of leukemia, higher levels of cancer-specific stress were associated with higher levels of depressive symptoms, sleep problems, and fatigue interference.…”
Section: Discussionmentioning
confidence: 56%
“…The experience of a diagnosis of cancer and its related treatments reportedly can lead to symptoms of posttraumatic stress in 7.3% to 35.2% of patients with cancer . In the current study, cancer‐specific stress (ie, total score on the IES‐R) uniquely explained approximately 3.2% of the variance in symptom burden.…”
Section: Discussionmentioning
confidence: 56%
“…A systematic review of 47 articles found that BC patients simultaneously reported PTSS and PTG, which evidenced PTSS and PTG often coexist in BC patients . Many research investigations in the field of trauma psychology has focused on the relationship between PTSS and PTG, with positive association, negative association, U‐shaped curvilinear association, and no association reported across studies.…”
Section: Introductionmentioning
confidence: 99%
“…A recent term for the positive psychological changes individuals experience following stressful events, coined by Tedeschi and Calhoun, is posttraumatic growth (PTG). Posttraumatic growth is defined as “the experience of positive change that occurs as a result of the struggle with highly challenging life crises.” Evidence suggests that PTG is relatively common among women with breast cancer and exhibits an increasing tendency among early‐stage breast cancer survivors over a 6‐month period . Posttraumatic growth has many related factors, such as age, education, economic status, treatment, social support, and support from significant others …”
Section: Introductionmentioning
confidence: 99%